Why do men who have sex with men test for HIV infection? Results from a community-based testing program in Seattle - Katz, David A. (2013)
BACKGROUND: The Centers for Disease Control and Prevention recommends at least annual HIV testing for men who have sex with men (MSM), but motivations for testing are not well understood. METHODS: We evaluated data from MSM testing for HIV at a community-based program in King County, Washington. Correlates of regular testing were examined using GEE regression models. RESULTS: Between February 2004 and June 2011, 7176 MSM attended 12,109 HIV testing visits. When asked reasons for testing, 49% reported it was time for their regular test, 27% reported unprotected sex, 24% were starting relationships, 21% reported sex with someone new, 21% sought STI/hepatitis screening, 12% reported sex with an HIV-infected partner, 2% suspected primary HIV infection, and 16% reported other reasons. In multivariable analysis, factors associated with regular testing included having a regular healthcare provider and the following in the previous year: having only male partners, having ≥10 male partners, inhaled nitrite use, not injecting drugs, and not having unprotected anal intercourse with a partner of unknown/discordant status (p≤0.001 for all). Men reporting regular testing reported shorter intertest intervals than men who did not (median of 233 vs. 322 days, respectively; p<0.001). CONCLUSIONS: Regular testing, sexual risk, and new partnerships were important drivers of HIV testing among MSM, and regular testing was associated with increased testing frequency. Promoting regular testing may reduce the time that HIV-infected MSM are unaware of their status, particularly among those who have sex with men and women or inject drugs.